Inflammasome activation as a link between obesity and thyroid disorders: Implications for an integrated clinical management - Le Moli, Rosario; Vella, Veronica; Tumino, Dario; Piticchio, Tommaso; Naselli, Adriano; Belfiore, Antonino; Frasca, Francesco (Frontiers in Endocrinology, 2022)
Obesity is strongly associated with a chronic low grade inflammatory state. Some experimental data indicate a relationship between obesity and thyroid diseases. Obese patients have an increased risk to develop thyroid autoimmunity and to became hypothyroid. These observations suggest a pathogenetic link between obesity, inflammation and autoimmunity. Moreover, type 2 diabetes and dyslipidemia, that are related to a low grade inflammatory state, were recently associated with more aggressive forms of autoimmune thyroid related disease such as Graves’ ophthalmopathy. The association between obesity and thyroid autoimmune diseases may be also in the opposite direction: treatment of autoimmune hyper and hypothyroidism may result into weigh gain. In addition, restoration of euthyroidism by T4 replacement therapy is more difficult to be achieved in obese athyreotic patients, as it is difficult to maintain thyrotropin stimulation hormone (TSH) values within normal range. It is also interesting to note that pro-inflammatory cytokines are decreased in obese patients after bariatric surgery along with a significant reduction in TSH levels. Moreover, the risk of thyroid cancer is increased in thyroid autoimmune disases and it is also related to the degree of obesity and inflammation. Molecular studies reveal a relationship between the low-grade inflammatory state of obesity and the presence of intracellular multiprotein complexes typical of immune cells (inflammasome). We now will highlight some clinical implication of inflammasome activation in the relationship between obesity and thyroid disease.